Kegiatan peduli anak stunting (PEDAS) dengan pemenuhan gizi dari bahan pangan lokal - Anggunan, Anggunan; Fransiska, Amelia; Hanafi, Ari Eka; Septiani, Ayu Aulia; Indriana, Danti; Gunawan, Muhammad Arfan; Putra, Ramanda Hadi; Maharani, Reysha Putri; Syahrin, Tiara Laili Alfy (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Stunting is a condition of growth failure in toddlers due to chronic malnutrition and frequent recurrent infections, especially during the first 1,000 days of life. Stunting is characterized by a child's height being lower than the standard for their age. The impact is not only physical, but also cognitive development and future productivity. Stunting remains a significant health problem in Negara Batin Village, West Kota Agung District, Tanggamus Regency. This condition is closely related to the community's lack of understanding regarding balanced nutrition, parenting practices, and environmental health. Purpose: To increase community knowledge about stunting prevention through nutrition education and nutritious food processing practices based on local ingredients. Method: The